STUDI SOSIOLOGIS TENTANG PENGELOLAAN KEBERSIHAN PADA PASAR TRADISIONAL DI KOTA PEKANBARU (Studi Kasus di Pasar Cik Puan, Pasar Pagi Dupa, dan Pasar Sail) - Zamzammi, Syukron; Asriwandari, Hesti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Cleanliness traditional market became one of the environmental problems in the city Pekanbaru. Traditional market conditions are squalid and filthy negative impacton health and eliminating the beauty of a city. This study aims to determine the form of hygiene management effort, in traditional markets, to know the constraints in the management of hygiene in traditional markets, and the role of merchants increating hygiene traditional markets in the city Pekanbaru. This research qualitative research using case studies. The Process of data collection is one by several techniques, interviews, and documentation related to the research topic. Sampling technique was used purposive sampling, so that samples taken truly representative and find out what researchers need. respondent of this study consists of 1 key informants, and 12 informants.From the research findings hygiene management in traditional markets, namely the provision of labor market cleaning personnel, provision of sanitary facilities market, the application of hygiene regulations market, collecting dues levy cleanliness, and hygiene monitoring market. Constraints in traditional markets hygiene management can be said to exist. Constraints that occur in the management of hygiene such as the availability of sanitary facilities market, environmental factors can not be predicted that the rain, and the low level of participation of both traders and visitors to the market to keep clean. Cleanliness is inseparable from the role of market traders to keep the markets where they sell. The role of merchants in maintaining the cleanliness of the traditional markets in the city of Pekanbaru can be said to be good. Role of the efforts made traders in traditional markets such as creating hygiene; throw trash in its place merchandise, Provide temporary landfills, pay the levy hygiene market, reprimanding people who throw litter, and participating merchants selling cleaning the place.Keywords: Traditional Market, cleanliness, Role, merchant